IDENTIFIKASI DAN KARAKTERISASI SAWAH TEKNIS DAN NON TEKNIS BERBASIS SIG (SISTEM INFORMASI GEOGRAFIS) DI SUB-DAS BILA - -, Rusdianto; Asra, Reza; Thamrin, Nining Triani; Mubarak, Husnul (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2024)
The relationship between watersheds (DAS) and rice fields, namely watersheds is a shallow water area whose topography is dominated by mountains, mountain ridges that collect and store rainwater before being released to rice fields through the main river. This study aims to identify GIS based technical and non-technical rice fields, and analyze the characteristics of technical and non-technical rice fields from various aspects. This study uses a quantitative descriptive approach method based on geographic information systems (GIS). Interpretation of sentinel 2A image data was then digitized onscreen to produce a map of rice fields. Then to identify technical and non-technical rice fields, onscreen digitization was carried out with the help of interviews with related agencies. Characteristic analysis was carried out by overlaying slope slope maps, elevation and soil types to identify the biophysical characteristics of the land, while economic characteristics and management were carried out by interview method. The total area of rice fields in the Bila Sub-Watershed is 5842.35 ha. Non-technical rice fields have an area of 2777.97 ha and technical 3064.38 ha. Non-Technical Rice Fields which dominate at a flat slope of 0-8% covering an area of 1637.05 ha (28.02%). Likewise, technical rice fields with a flat slope of 0-8% cover an area of 2393.76 ha (40.97%). Non-technical rice fields dominate at an altitude of 0-500 above sea level (with an area of 2643.66 ha (45.25%). Likewise, technical rice fields 0-500 above sea level, with an area of 3061.55 ha (52.4%). Non-technical rice fields have dystropepts soil types 527.73 ha 9.03%, 1.09 (ha) 0.02% Eutropepts, 1280.05 (ha) 21.91% Paleudults, tropaquepts 104.36 (ha) 1.79%,272.99 (ha) 4.67% Tropudalfs, 591.73 (ha) 10.1% Tropudults. Technical with an area of 1078.16 ha 18.48% Paleudults and 1986.22 ha 34% Tropaquepts. Planting is carried out 2 times a year, both technical and non-technical rice fields. For the provision of water to non-technical rice fields, it only relies on rainwater for rice field needs. Meanwhile, technical rice fields rely on water from irrigation networks, pipes and pumping machines as auxiliary tools.